STRATEGI KOMUNIKASI WISATA TAMAN AIR MANCUR SRI BADUGA SITU BULEUD KABUPATEN PURWAKARTA: Anisya Wulandari, Itca Istia Wahyuni - Anisya Wulandari; Itca Istia Wahyuni (Commed : Jurnal Komunikasi dan Media, 2018)
This research was motivated by Situ Buleud is not so well known to the public then was built and developed into a Sri Baduga Fountain Park requires communication to the target audience to come to Purwakarta District. This research uses qualitative research methodology with qualitative descriptive approach. The purpose of this research is to describe and analyze the communication strategy of Sri Baduga Situ Buleud Fountain Park. The object of this research is communication strategy of DISPORAPARBUD and DISKOMINFO Purwakarta District. This session will discuss about five stage of communication plans are research, plan, execute, measure, and report. The result found that research which has been done by DISPORAPARBUD are observation and the evaluation result of the number of tourists and DISKOMINFO take the data from the monitoring media report. DISPORAPARBUD and DISKOMINFO Purwakata District has been planned to determine the source or communicator, message, media, target, and effects. The execute stage will be performed after getting approval from Purwakarta Regent by implementing the plan that has been designed. In this Measure stage, DISPORAPARBUD will count the total of tourist, while tourism media will be monitored by DISKOMINFO Purwakarta district. Report undertaken by DISPORAPARBUD Purwakarta District, conduct an evaluation by counting the number of tourists in each week and will be made a report at the end of each year. Therefor DISKOMINFO Reporting as a book report on the results of analysis from third parties